LogoLounge 3 : 2,000 international identities by leading designers - Fishel, Catharine M. (Rockport Publishers, 2011)
Now in a new "mini" edition, this third volume in the best-selling LogoLounge series provides 2,000 totally new logos from designers worldwide.